Arctic Ocean floor / produced in the Geographic Art Division, National Geographic Society - Berann, Heinrich C.; Boberschmidt, Leo J.; Heezen, Bruce C.; Tharp, Marie (Washington, D.C. : National Geographic Society, 1971)
October 1971 Relief shown by land form drawings, shading, and spot heights. Depths shown by land form drawings, shading, and soundings. On verso is col. map of "Arctic Ocean" with historical and descriptive notes. Color 1:10,011,000